2020
DOI: 10.1109/jtehm.2020.3014564
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Device-Independent Next Day Activity and Next Night Sleep Prediction for Rehabilitation Populations

Abstract: Wearable sensor-based devices are increasingly applied in free-living and clinical settings to collect fine-grained, objective data about activity and sleep behavior. The manufacturers of these devices provide proprietary software that labels the sensor data at specified time intervals with activity and sleep information. If the device wearer has a health condition affecting their movement, such as a stroke, these labels and their values can vary greatly from manufacturer to manufacturer. Consequently, generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Further research is needed to examine sleep intervention effectiveness and resulting behavior change based on sleep feedback and monitoring. 63,64 The positive correlation of strengths, challenges, and needs was an unexpected finding and suggests the SS group may have increased self-awareness and engagement related to their health. This finding aligns with the literature that women with CVD need and desire information about their condition, ongoing support, and a strengths-based approach to their care.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Further research is needed to examine sleep intervention effectiveness and resulting behavior change based on sleep feedback and monitoring. 63,64 The positive correlation of strengths, challenges, and needs was an unexpected finding and suggests the SS group may have increased self-awareness and engagement related to their health. This finding aligns with the literature that women with CVD need and desire information about their condition, ongoing support, and a strengths-based approach to their care.…”
Section: Discussionmentioning
confidence: 94%
“…Both of these findings suggest that having data regarding women's sleep challenges and needs would inform clinical practice, to ensure that consumers and clinicians have meaningful and relevant conversations regarding sleep health and related interventions, particularly for women with CVD. Further research is needed to examine sleep intervention effectiveness and resulting behavior change based on sleep feedback and monitoring 63,64 …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, research has indicated that some individuals may engage with certain apps (eg, calorie-tracking apps) in different ways around binge-eating episodes [ 1 ]. Similarly, certain episodes could happen around indicators related to physical activity, sleep disorders, or communication patterns that previous research has had positive results quantifying using smartphones and wearables [ 47 , 59 , 85 - 87 ], which are a more direct measurement of the observed phenomena compared with affect and psychological constructs.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the main problem Sangavi S. ( 2019); Alrazzak and Alhalabi (2019); Fellger et al (2020); Kolkar and Geetha (2021); Das et al (2023) inherent in the development of assistive technologies adapted for home care concerns artificial intelligence models allowing real-time recognition of a person's ongoing Activities of Daily Living (ADLs). Few examples could be: preparing a meal, washing hands, taking medication, etc.…”
Section: Related Workmentioning
confidence: 99%